Identity Processes and Parent–Child and Sibling Relationships in Adolescence: A Five‐Wave Multi‐Informant Longitudinal Study. Issue 1 (20th May 2016) - Crocetti, Elisabetta; Branje, Susan; Rubini, Monica; Koot, Hans M.; Meeus, Wim
Abstract : The purpose of this study was to examine reciprocal associations between identity processes (commitment, in‐depth exploration, and reconsideration of commitment) and dimensions (support, negative interaction, and power) of maternal, paternal, and sibling relationships. A total of 497 Dutch families including 14‐years‐old adolescents (56.9% males), their fathers, mothers, and siblings, for a total of 1, 988 respondents, participated in a five‐wave longitudinal study. Cross‐lagged analyses indicated that commitment and in‐depth exploration predicted improvements in family relationships (unidirectional effects), whereas reconsideration of commitment was predicted by low levels of maternal support and worsened the quality of the paternal relationship (reciprocal effects). These results were not moderated by adolescents' gender and sibling characteristics. Theoretical and practical implications are discussed.